The reflection of competitive anxiety on the levels of attention of senior football players - مجادي, مفتاح (sports creativity, 2025)
The study aimed to know the reflection of the factors causing competitive anxiety on the levels of attention of football players, where the researcher relied on the appropriate descriptive approach for such studies using a questionnaire directed to the players. Secondly, he concluded that public pressure has a negative impact on the degree of attention to the players during the interview, as well as the importance of the interview negatively reflecting on the focus of attention among the players, and the weak arbitration raises anxiety among the players during the competition, which distracts their attention